Black Water Purification by Activated Carbon from Ilalang Weeds (Imperata cylindrica) Adsorbent in Peatland Rural Area - Ngatijo Ngatijo; Heriyanti Heriyanti; Winda Arinda Putri; Aslan Irunsah; Bayu Ishartono; Rahmat Basuki (Jurnal Riset Kimia, 2022)
The black water containing humic acid, HA in peat land rural area is a serious issue. This study aims to synthesis of activated carbon, AC from Ilalang Weeds, IW (Imperata cylindrica) as low-cost adsorbent for HA. The success AC synthesis by H3PO4 activator from IW was evidently characterized by Fourier Transform Infra-Red, FTIR and Scanning Electron Microscopy, SEM. The effects of pH solution, initial HA concentration, and contact time were systematically studied to investigate the performance of Activated Carbon from Ilalang Weeds, ACIW. The results showed the increasing of Langmuir monolayer capacity of HA adsorption on carbon from IW before (49.75 mg g-1) and after (56.82 mg g-1) activation process at the pH optimum 6.0. The equilibrium adsorption data fitted with the isotherm model was shifted from multilayer Freundlich model (CIW) into monolayer Langmuir model as the consequences of increasing pore diameter size and active sites intensity. Calculation of adsorption energy by Dubinin-Radushkevich (EDR) model, 0.50 and 2.24 kJ mol-1 for CIW and ACIW, respectively, showed the increasing of physical affinity of HA with the active sites of adsorbent. Adsorption kinetics showed that the adsorption behavior followed the Ho pseudo-second-order kinetic model. The experimental results of this work demonstrate that the ACIW can be used as a promising low-cost adsorbent for HA removal for clean water production in peat land rural area.Â